2011
DOI: 10.1017/s0373463311000324
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Mitigation of the Main Errors for Centimetre-level Compass RTK Solutions over Medium-Long Baselines

Abstract: Centimetre-level RTK solutions are mainly influenced by satellite orbit errors, ionospheric and tropospheric delays, and measurement noise (including multipath effects). Estimation and mitigation of the main errors for the CM-level Compass RTK solutions over medium-long baselines are investigated. Tests conducted for this research lead to the following conclusions: 1.For 100 km baselines, a 4 cm error in height component will be induced by a 10 m orbit error. For longer baselines, rapid precise ephemeris will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Some BeiDou results can be found in the literature, where we have simulation results in Grelier et al (2007), Huang and Tsai (2008), Cao et al (2008), Chen et al (2009), Feng and Li (2010), Zhang et al (2010), Guo et al (2011), Yang et al (2011) and Qu et al (2012). Real data results were presented by Shi et al (2013), who evaluated BeiDou-only Single Point Positioning (SPP), relative code positioning and Real-TimeKinematic (RTK).…”
Section: Introductionmentioning
confidence: 54%
“…Some BeiDou results can be found in the literature, where we have simulation results in Grelier et al (2007), Huang and Tsai (2008), Cao et al (2008), Chen et al (2009), Feng and Li (2010), Zhang et al (2010), Guo et al (2011), Yang et al (2011) and Qu et al (2012). Real data results were presented by Shi et al (2013), who evaluated BeiDou-only Single Point Positioning (SPP), relative code positioning and Real-TimeKinematic (RTK).…”
Section: Introductionmentioning
confidence: 54%
“…On the basis of triplefrequency combination model of BDS above, according to the selection criteria and constraint conditions of combination coefficients [14,17], considering the properties of (7) and ensuring the magnitude of error TC is of cm level, the combination coefficients and their other properties of some wide-lane (WL) and extra-wide-lane (EWL) of BDS triplefrequency combination are listed in Table 2. In order to realize precise orbit determination for BDS MEO satellites, if we choose the EWL of B2-B3 carrier combination in Table 2, (17) can be recovered as follows:…”
Section: The Precision Orbit Determination Model Of Triple-frequency mentioning
confidence: 99%
“…It has been found that atmospheric bias affect more error in vertical component rather than in horizontal component which up to several decimeters in RTK GNSS positioning [20,21]. Fig.…”
Section: Introductionmentioning
confidence: 95%